2021
DOI: 10.3390/biomedicines9040346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Oral Probiotic Treatment in Paclitaxel-Induced Neuropathic Pain

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) represents one of the most prevalent and potentially disabling side effects due to the use of anticancer drugs, one of the primary neuropathies detected is peripheral neuropathy induced by administration of taxanes, including paclitaxel. It has been demonstrated that gut microbiota is crucial for the therapeutic effect of chemotherapeutic drugs for inhibiting tumor growth and contributed to the pathogenesis of the CIPN. The use of nutraceuticals has receiving g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 82 publications
(102 reference statements)
1
25
0
1
Order By: Relevance
“…A recent study showed decreased transcription factor in parallel with reduced expression of PPAR-γ in spinal cords after paclitaxel administration. In the same study, it is also observed that administration of probiotic formulation, SLAB51 reduced serum cytokine levels and increased PPAR- protein levels in spinal cord [36]. In accordance with previous studies, it seems activation of PPAR- relieved neuropathic pain state, possibly through an inhibitory action on neuro-immune glial activation and subsequent TNF-α release in spinal cord.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study showed decreased transcription factor in parallel with reduced expression of PPAR-γ in spinal cords after paclitaxel administration. In the same study, it is also observed that administration of probiotic formulation, SLAB51 reduced serum cytokine levels and increased PPAR- protein levels in spinal cord [36]. In accordance with previous studies, it seems activation of PPAR- relieved neuropathic pain state, possibly through an inhibitory action on neuro-immune glial activation and subsequent TNF-α release in spinal cord.…”
Section: Discussionsupporting
confidence: 85%
“…Recent evidence suggests that dysbiosis exists in several types of CNP and cognitive impairments (Jiang et al, 2017 ; Lin et al, 2020 ; Marttinen et al, 2020 ) . Moreover, the interventions of gut microbiota, such as probiotics and fecal microbiota transplantation (FMT), showed beneficial effects on the two disorders (Van Laar et al, 2019 ; Bonomo et al, 2020 ; Cuozzo et al, 2021 ). Studies have also revealed that gut microbiota regulates the development of CNP or cognitive impairment through the vagus nerve, endocrine, and metabolic as well as immune communications (Sampson and Mazmanian, 2015 ; Sun et al, 2020 ; Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, altering the gut microbiome population by administration of locally-acting antibiotics or by probiotics has been shown in preclinical and clinical studies to attenuate stress-induced visceral hyperalgesia, 22 , 23 , 30 , 41 as well as attenuate neuropathic cutaneous mechanical allodynia and thermal hyperalgesia. 42 , 43 How probiotic and antibiotic administration can ameliorate hyperalgesia, which is currently unknown, may depend on more than one mechanism. One mechanism may depend on modifying stress-induced gut dysbiosis.…”
Section: Discussionmentioning
confidence: 99%